A Primer on the Economics of Shale Gas Production Just How Cheap is Shale Gas?. Issue 4 (December 2013) - Lake, Larry W.; Martin, John; Ramsey, J. Douglas; Titman, Sheridan
<x xml:space="preserve">Abstract</x> The authors analyze the economics of natural gas production in the U.S. in light of the government's recent dramatic upward revisions in gas reserve estimates as a result of advances in horizontal drilling and fracturing ("fracking"). While some observers believe the U.S. will enjoy very large supplies of low‐priced gas for a long time to come, others are not so sure. Using the data from gas wells completed in the Haynesville shale of northern Louisiana, the authors offer a probabilistic and economic perspective on these newly accessible reserves. Their model and NPV simulations indicate that shale gas exploitation is probably sustainable (with a 60% likelihood), but with some important reservations. NPVs are highly sensitive to gas price assumptions and projected production volumes. The authors' base case assumes the continuation into the foreseeable future of the current gas futures price curve; but the authors also point out that a fall in price of just 17% along that curve would reduce well NPVs to zero. Although it is clear that production from shale wells declines more rapidly than production from conventional wells, engineers have too little history with shale wells to forecast ultimate production with great confidence. Nevertheless, shale gas drilling opportunities also present energy companies with valuable "follow‐on" real options that are not captured in NPV analysis. This additional source of value is inherent in vast shale gas formations in which successful wells tend to lead to more development opportunities.